Beyond “Driving While Black” and “Flying While Brown”: Using Intersectionality to Uncover the Gendered Aspects of Racial Profiling - Sharma, Sherri (Columbia Journal of Gender and Law, 2003)
The day after the September 11 th terrorist attacks in New York, two Muslim women in veils were pushing baby strollers in Brooklyn when they were surrounded by a group of angry youths who harassed them with racial epithets. A week later, Sonia Sudan, a South Asian high school student in Boca Raton, Florida, was at a Kinko’s copy shop when she was hauled out of the store by a deputy and held in a squad car until the FBI arrived and released her. Sonia was having cards printed for her boyfriend, who was about to enter the Air Force. She had illustrated them with a pentagram modeled after a piece of his jewelry, and a store employee had called the police, claiming S onia was drawing satanic s ymbols. In addition, during the last week of September 2001, a Muslim Harvard graduate student was verbally and physically assaulted as she exited a subway station in Cambridge, Massachusetts. She was wearing the hijab. Four white men cornered the woman and shouted, “What are you doing here? Go home to your own country!” and then tried to remove her hijab. Since the September 11th terrorist attacks, incidents like these are numerous. Arab Americans, or anyone who resembles one, male or female, are being “profiled.” Yet the primary focus of racial profiling has been on the male members of these communities. This focus is not surprising given the popular and legal understanding o f racial profiling a s a state practice that targets men of color.